2021
DOI: 10.1136/bmj-2021-068665
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 vaccination and myocarditis or myopericarditis: population based cohort study

Abstract: Objective To investigate the association between SARS-CoV-2 vaccination and myocarditis or myopericarditis. Design Population based cohort study. Setting Denmark. Participants 4 931 775 individuals aged 12 years or older, followed from 1 October 2020 to 5 October 2021. Main outcome measures The primary outcome, myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
235
2
9

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(262 citation statements)
references
References 19 publications
16
235
2
9
Order By: Relevance
“…The authors concluded that vaccination with mRNA-1273 was associated with a significantly increased risk of myocarditis or myopericarditis in the Danish population. However, the overall risks are low and must be balanced against the individual and societal benefits associated with vaccination [23].…”
Section: Emerging Etiologies and Pathophysiology Of Myocarditismentioning
confidence: 99%
“…The authors concluded that vaccination with mRNA-1273 was associated with a significantly increased risk of myocarditis or myopericarditis in the Danish population. However, the overall risks are low and must be balanced against the individual and societal benefits associated with vaccination [23].…”
Section: Emerging Etiologies and Pathophysiology Of Myocarditismentioning
confidence: 99%
“…Myocarditis observed in the days following the injection of messenger RNA vaccine in young individuals is another well-established rare complication, first identified within the Israeli health system [ 5 ]. The higher risk with the mRNA-1273 (Moderna) vaccine as compared to the BNT162b2 (Pfizer/BioNTech) vaccine [ 6 ] led several countries to only use the BNT162b2 vaccine in younger individuals and to cut the dose of the mRNA-1273 vaccine by half when given as a booster.…”
mentioning
confidence: 99%
“…What if you wrongly advise millions of people, on national television, about the efficacy of vaccines (https://www.sciencemediacentre.org/expert-reaction-to-a-doctor-challenging-the-health-secretary-sajid-javid-on-compulsory-vaccination-at-kings-college-hospital)?4 Or fail to stay up to date with the latest research on vaccines and myocarditis (doi:10.1136/bmj-2021-068665)?5 Perhaps you need an update on management of chronic anal fissures (doi:10.1136/bmj-2021-066834) and extreme preterm birth (doi:10.1136/bmj-2021-055924)?67 How about the company executives refusing scrutiny of their trial data while profiting by the billion (doi:10.1136/bmj.o102)?8 Or the editors, journalists, and politicians unwilling to cover the growing concern about China’s human rights abuses (doi:10.1136/bmj.o44)?9 What of Facebook’s responsibility in trying to censor legitimate concerns about the conduct of clinical trials (doi:10.1136/bmj.o95)?10…”
mentioning
confidence: 99%